Vollenhoven. The development of a pleasure garden in the range of hills called ‘Utrechtse Heuvelrug’ in the first half of the nineteenth century (Bulletin KNOB, 2007)
Vollenhoven in De Bilt is one of the country estates that earned the region between Utrecht and Wageningen the name 'Stichtse Lustwarande' (pleasure grounds). The country estate consists of a distinguished residence, a landscape park with various ancillary buildings such as an orangery, a coach house and an ice house, the house of the master carpenter, as well as a very beautiful vegetable garden with glasshouses.Vollenhoven has had a long series of proprietors; it seldom remained in one and the same family for longer than one generation. As many of the proprietors contributed to the development of the country estate, its history cannot be summarized in a few lines. However, two of the earlier proprietors have particularly left their mark on the country estate and the structures erected on it: Pieter de Smeth van Alphen and Goderd van der Capellen van Berkenwoude.Until recently little was known about the development of the country estate in the nineteenth century. From the seventeenth century there had already been a building here, a small farmhouse. It is assumed that the house in its present appearance was realized in the nineteenth century. B.W.H. Ziesenis, who worked in the region around 1800, is suggested as the architect.Hendrik van Lunteren seems to be the most likely architect of the landscape park, but there was no solid evidence of this. His name was correctly linked with it, as appears from Van Lunteren’s original draft map for the landscape park from around 1828, which was discovered in the attic of Vollenhoven in 2005. It also appeared that there had been a park with a landscape layout previously.This raises new questions, for instance, whether several layers are to be distinguished in the landscape park and when it started to acquire the qualities of a landscape. Among the residents of Vollenhoven tradition has it that in the early nineteenth century Pieter de Smeth was the founder of the house and the park and that Goderd van der Capellen expanded and completed the country estate.In this article the development of Vollenhoven from a simple farmhouse into a pleasure garden is described on the basis of records, inventories and comparisons of historical maps and literature.